Colonização e infecção em pacientes com cateter peridural não tunelizado para analgesia - Diccini, Solange [UNIFESP] (2010)
OBJECTIVE: To correlate the colonization and infection in patients using non-tunneled epidural catheter for analgesia effects. METHODS: This is a prospective study of 109 clinical or surgical patients, with catheter dwell time> 72 hours, in a private hospital in the city of São Paulo. The culture of surveillance was carried out based on the collection of the epidural catheter tip, swab peri-catheter and peripheral blood cultures. RESULTS: Among the 109 patients accompanied, 106 (97.2%) were surgical and 3 (2.8%) clinical. The catheter dwell time ranged from 3 to 18 days and the rate of colonization was 11%. Twelve patients had epidural catheter colonization and the main organism isolated was coagulase-negative Staphylococcus. CONCLUSIONS: The positive culture of epidural catheter was a predictive factor for colonization; however, it was not found positive patients who evolved to infection.